THE ANALYSIS AND MULTI-CRITERIA SCHEDULING OF THREADS IN THE TRANSPORT NETWORK TAKING INTO ACCOUNT THE INTERVAL OF UNCERTAINTY - Panyk, L. O. (Science and Transport Progress, 2008)
In the article a method is developed and the multicriterion analysis of streams is executed in network models in the conditions of unclear (interval) basic data.